Carinal Resection and Reconstruction for Tracheo-bronchial Neoplasms—Surgical Outcomes of 20 Consecutively Operated Cases - Pulle, Mohan Venkatesh (Indian J Surg Oncol, 2020)
Carinal resections for trachea-bronchial neoplasms are technically challenging and have high operative morbidity and mortality. This study examines the clinical experience of carinal resections for various tracheo-bronchial tumors in a dedicated thoracic surgery center. Medical records were retrospectively reviewed from March 2012 to December 2019 to identify all patients who underwent carinal resection. An analysis of demographic characteristics, perioperative variables including complications, was carried out. Perioperative outcome was the primary outcome measure. Twenty carinal resections were performed with a median follow-up of 2.4 years (range 0.5–4.1). Procedures included 8 isolated carinal resections (40%), 6 right carinal pneumonectomy (30%), 1 left carinal pneumonectomy (5%), and 5 carinal right upper sleeve lobectomy (25%). Age of the patients range from 18 to 62 years with 9/11 male-female ratio. Mean duration from symptom onset to diagnosis was 6.1 months. All post-operative complications occurred in 7 (35%) patients. Anastomotic complications occurred in 2 (10%) patients. Out of these, 1 patient was initially managed with stent placement, ultimately requiring pneumonectomy. Post-operative events were significantly higher in group of patients who underwent carinal resection with concomitant pulmonary resection (P = 0.01). No perioperative (90-day) mortality was found. Despite advances in perioperative management, carinal resection poses challenges for both patient and surgeon. Concomitant pulmonary resection was associated with increased risk of peri-operative complications. Appropriate patient selection, meticulous surgical technique, and stringent post-operative protocols are the key for success.